1998
DOI: 10.1111/j.1440-1681.1998.tb02349.x
|View full text |Cite
|
Sign up to set email alerts
|

The Nitric Oxide System and Cortisol‐induced Hypertension in Humans

Abstract: 1. The aim of the present study was to assess the role of the nitric oxide (NO) system in cortisol-induced hypertension in humans. 2. Plasma and urinary nitrate/nitrite concentrations and plasma concentrations of arginine and symmetric (SDMA) and asymmetric (ADMA) dimethyl arginine were measured in six subjects on a restricted nitrate diet who were treated with 80 mg/day cortisol and in subjects on an unrestricted nitrate diet who were treated with cortisol (80 mg/day, n = 6, or 200 mg/day, n = 10) for 5 days.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
53
0

Year Published

2000
2000
2020
2020

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 77 publications
(56 citation statements)
references
References 6 publications
3
53
0
Order By: Relevance
“…The lower cortisol levels in females are in accordance with the perception of an ongoing and unavoidable stress situation, but is however not associated with an increase in blood pressure levels or increased vascular responsiveness. 22,28 The lower testosterone and higher prolactin levels in females are in accordance with vasoconstriction and therefore with increased DBP reactivity and TPR reactivity. 40 This may interfere with blood pressure, and these parameters are therefore associated with the high rate of hypertension in stratum 3 subjects.…”
Section: Malesmentioning
confidence: 93%
See 1 more Smart Citation
“…The lower cortisol levels in females are in accordance with the perception of an ongoing and unavoidable stress situation, but is however not associated with an increase in blood pressure levels or increased vascular responsiveness. 22,28 The lower testosterone and higher prolactin levels in females are in accordance with vasoconstriction and therefore with increased DBP reactivity and TPR reactivity. 40 This may interfere with blood pressure, and these parameters are therefore associated with the high rate of hypertension in stratum 3 subjects.…”
Section: Malesmentioning
confidence: 93%
“…The nitric oxide system may also play a role in cortisol-induced hypertension. 28,29 It is also reported that cortisol is not a direct determinant of blood pressure, but cortisol may regulate other key components of vascular risk such as low high-density lipoprotein (HDL) cholesterol and fat distribution. 30 Heightened prolactin levels are also associated with powerless situation stress.…”
Section: Introductionmentioning
confidence: 99%
“…1,3 Cortisol treatment also causes suppression of the nitric oxide system as evidenced by reduced plasma nitrate/nitrite concentrations. 5 In the context of these observations, Correspondence 6,7 EPO-induced hypertension has also been demonstrated to be due in part to nitric oxide resistance. 8 The aim of the current study was to examine the role of EPO as a possible mediator of cortisolinduced hypertension.…”
Section: Introductionmentioning
confidence: 99%
“…4 In humans, cortisol-increases in blood pressure occur in association with reductions in plasma nitrate/nitrite concentrations, but no change in plasma arginine or symmetric or asymmetric dimethyl arginine has been observed, indicating that the reductions in nitrate could not be explained by changes in substrate availability or endogenous nitric oxide synthase inhibitors. 5 More recently, using bilateral forearm plethysmography, we have found impaired cholinergic vasodilatation after cortisol administration. Cortisol did not affect the response to sodium nitroprusside, and although N G -monomethyl-L-arginine inhibited cholinergic vasodilation in placebo-treated subjects, it had no additional effect in the presence of cortisol.…”
mentioning
confidence: 99%